An analysis of thermal comfort in primary schools in Vietnam - Le, Thi Ho Vi; Gillott, Mark C.; Rodrigues, Lucélia Taranto (2017)
There is a trend of installing air conditioning systems in public primary schools that are currently naturally ventilated in Vietnam. A previous study conducted by the authors provided evidence that there is limited need for air conditioning in Vietnamese mid-season and the hottest season.